Matriarchal Society in The Secret Life of Bees by Sue Monk Kidd - Teta Irama Setri; Dwi Budi Setiawan (Linguistics and Literature Students' Journal, 2020)
This research discusses a novel which written by Sue Monk Kidd entitled The Secret Life of Bees. The writers aims to describe the matriarchal society issue that is often regarded as the opposed of patriarchy. This research aims to answer the question how levels of matriarchal society described in the novel The Secret Life of Bees through women characters in the story. This study applies descriptive qualitative method and typically library research. This research applies socio-historical approach in order to look at the relation between literary work and society’s historical elements that happen in the past. At political level, August character shows as the matriarch or the leader in community with important role for overcoming conflict and decision making process. At economical level, it shows that matriarchal society common practice has right and same position in economic affair and giving gift each other to make the economic condition balance. Last, at spiritual and cultural level, it is described that women characters in The Secret Life of Bees believe in feminine divine which is the Black Mary and doing worship for her. In conclusion, The Secret Life of Bees novel clearly depicts matriarchal society based on the theory of Matriarchy by Heide Göettner-Abendroth.Keyword: The Secret Life of Bees, Matriarchy, Matriarchal Society, Levels of Matriarchal Society, Socio-historical Approach